Implementation of Total Quality Control Products at PT. XYZ - Adisuputra Adisuputra (JEM Jurnal Ekonomi dan Manajemen, 2019)
Product quality is the ability of a product or service in carrying out its functions both durability, reliability, accuracy, ease of operation, repair, and other valuable attributes. The company can implement the Total Quality Management program in improving the quality of its products. This study uses a literature study approach and confirms on practice data, steps in the production process in accordance with the PDCA cycle and see whether quality planning has followed the 5W + 1H principle. Data is processed using Fishbone Diagrams to analyze the causes and effects that will affect product quality. The results of the study concluded that integrated Quality Control is needed to continuously improve quality standards from all aspects.